Design and Construction of Monitoring and Control System in Swallow House Based on IoT - Al Dimas Sausan Roidoh; Sihombing, Marto; Milli Alfhi Syari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This study aims to design and build an Internet of Things (IoT) based monitoring and control system in a swiftlet building. Swiftlet nest farming is a rapidly growing industry in Indonesia, but still faces challenges in terms of monitoring and optimal environmental management for swiftlet productivity. The system developed integrates sensors to measure critical environmental parameters such as temperature. The research methodology includes hardware design using a microcontroller, sensors, and actuators connected to an IoT network. Software is developed to process sensor data, send it to blynk, and present information through a web interface that can be accessed remotely. This system is also equipped with an automatic control feature to keep environmental parameters within the optimal range. The results of the study show that the system is capable of real-time monitoring and providing notifications when an anomaly occurs. The automatic control feature successfully maintains temperature stability in the swiftlet building, where when the temperature read by the sensor is less than or equal to 25oC the lights will turn on and if the temperature is more than 29oC the lights will turn off. In conclusion, the implementation of this IoT-based monitoring and control system provides an effective solution to increase efficiency and productivity in swiftlet nest farming. This research opens up opportunities for further development in the application of IoT technology in the business sector, especially in swallow farming.